My fair ladies : female robots, androids, and other artificial Eves - Wosk, Julie (Rutgers University Press, 2015)
Taking us on a fascinating tour across a wide variety of media, from sci-fi films to underwear ads, My Fair Ladies introduces us to a bevy of lifelike, manmade women, from automatons to artificial intelligent robots. Julie Wosk considers how this figure of the "perfect woman" has come to embody not only fantasies, but also fears about gender and technology. In addition, she examines how female artists have subverted these images of the artificial woman that loom so large over real women's lives.